Serum Calprotectin as a Potential Predictor of Microvascular Manifestations in Patients with Antiphospholipid Syndrome - Zhao, Yuan; Qi, Wanting; Huang, Can; Zhou, Yangzhong; Wang, Qian; Tian, Xinping; Li, Mengtao; Zhao, Yan; Zeng, Xiaofeng; Zhao, Jiuliang (Rheumatology and therapy., 2023)
Introduction Microvascular manifestations constitute a subtype of antiphospholipid syndrome, and those patients have relatively poor prognoses, so it is important to find markers for microvascular manifestations. This study was conducted to explore whether serum calprotectin could be a predictor of microvascular manifestations in antiphospholipid antibody (aPL)-positive patients. Methods Consecutive patients with persistent aPL positivity referred to Peking Union Medical College Hospital and age- and sex-matched health controls (HCs) were included. Microvascular manifestations included antiphospholipid syndrome (APS) nephropathy, livedo reticularis, valvular lesions, non-stroke central nervous system manifestations, myocarditis, catastrophic APS, and other microvascular manifestations confirmed by pathology, imaging, or clinical diagnosis. Calprotectin was measured by an enzyme-linked immunosorbent assay (ELISA). The cutoff value was defined as mean + 2 standard deviations of HCs. Multivariable logistic regression analysis was used to analyze risk factors. Pearson correlation analysis was used to detect the correlation between calprotectin and other laboratory data. Results Of the 466 patients included in the study, 281 (60.3%) patients met the 2006 Sydney Revised Classification Criteria; among the latter, 77.2% were patients with primary APS. The mean age was 39.10 ± 13.05 years old, and 77.0% were female. Thirty-eight age- and sex-matched HCs were included in the study. Serum calprotectin levels were increased in aPL-positive patients compared with HCs (649.66 ± 240.79 vs 484.62 ± 149.37 ng/ml, p < 0.001), and were increased in patients with microvascular manifestations compared with patients without (693.03 ± 271.90 vs 639.43 ± 232.06 ng/ml, p = 0.044). The cutoff value was 783.36 ng/ml. Ninety-three patients (20.0%) were positive for calprotectin. Calprotectin positivity was independently associated with microvascular manifestations (odds ratio [OR] 1.90, 95% confidence interval [CI] 1.07–3.36) and platelet count (PLT) < 100 (OR 2.04, 95% CI 1.08–3.88). Age (OR 0.98, 95% CI 0.96–1.00), systemic lupus erythematosus (OR 2.08, 95% CI 1.15–3.75), calprotectin positivity (OR 1.83, 95% CI 1.02–3.26), hypertension (OR 2.73, 95% CI 1.36–5.45), hemolytic anemia (OR 2.66, 95% CI 1.13–6.23), and anti-β2GPI antibodies (OR 2.06, 95% CI 1.11–3.83) could independently predict microvascular manifestations in aPL-positive patients. Serum calprotectin negatively correlated with PLT ( R = − 0.101, p = 0.031). Conclusion Serum calprotectin levels are increased in aPL-positive patients and could be a potential predictor of microvascular manifestations.